Effect of combined shear stresses on the ultimate axial response of the double bottom of a containership - Bacoccoli, R.; Fujikubo, M.; GAIOTTI, MARCO; RIZZO, CESARE MARIO (ASME Publishing, 2016)
Ultimate strength of the hull girder of containerships became a significant issue in the last years in view of recent accidents and related investigations. Actually, larger and larger ships were put into service and still are designed and built. Recognizing such an issue, investigations were carried out and led to the issuance of a specific longitudinal strength standard for containerships by the International Association of Classification Societies [1]. Loading conditions become more and more challenging and especially combinations of various actions were found to impair the hull girder ultimate strength. In the attempt to better understand the influence of load combinations onto the ultimate strength of the hull girder, investigations were carried out. In this paper, the effects of the shear is considered using rather refined and accurate finite element models of a typical containership double bottom.